As-needed inhaled corticosteroids as add-on therapy versus SMART therapy: an evolving understanding of the two approaches in the management of moderate-to-severe asthma. Issue 3 (May 2023) - Salciccioli, Justin D.; Israel, Elliot
Abstract : Purpose of review: Asthma is the most common chronic respiratory disorder, characterized by recurring, reversible airflow obstruction due to inflammation and airway hyperresponsiveness. Although biologics have provided significant advances in the treatment of asthma, they are expensive, and their use remains restricted to more severe asthma. Additional approaches in the management of moderate-to-severe asthma are necessary. Recent findings: ICS–formoterol as maintenance and reliever therapy in asthma and its effect on improved asthma control has been demonstrated in multiple cohorts of asthma. Although ICS–formoterol as maintenance and reliever therapy has been widely validated, there are significant design considerations including the requirement for exacerbation and bronchodilator response and the lack of evidence for effectiveness in patients who use nebulized reliever therapies, which may limit the use of this therapy in selected populations. More recent trials of as-needed ICS have demonstrated effectiveness in reducing asthma exacerbations and improvements in asthma control and may provide an additional therapeutic strategy for individuals with moderate-to-severe asthma. Summary: Both ICS–formoterol as a maintenance and a reliever as well as as-needed ICS have demonstrated significant improvements in the control of moderate-to-severe asthma. Future investigational work will be necessary to elucidate whether a strategy of ICS–formoterol as maintenance and reliever therapy or an as-needed ICS strategy demonstrates superiority in asthma control in the context of the cost to individual patients and health systems.